Pengembangan Media Pembelajaran Animasi Game Berbasis Canva pada Materi Membaca dan Menulis Suku Kata pada Kelas 1 SDN Pakis V Surabaya - Riana, Aulia; Yuanta, Friendha; Bahtiar, Reza Syehma (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop Canva-based animated game learning media called Batulia Play for reading and writing syllables in grade 1 students of SDN Pakis V Surabaya. This type of research is a development research (Research and Development) that adopts the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), focusing on visual and interactive aspects to increase student motivation and learning outcomes. Media validation was conducted by media experts, material experts, and through student responses, followed by a pretest-posttest test to measure its effectiveness. The validation results showed an average percentage of 97% from media experts, 88% from material experts, and 92.73% from student responses, all included in the “Strongly Agree” category. After using Batulia Play media, student learning outcomes increased by 11.38%. Thus, Batulia Play media is proven to be feasible and effective in learning to read and write syllables in grade 1 SDN Pakis V Surabaya.